Risk Factors and Clinical Outcomes of Candidemia Associated With Severe COVID-19. (13th September 2022) - Dixit, Deepali; Jen, Polly; Maxwell, Tyler D.; Smoke, Steven; McCracken, James Andrew; Cardinale-King, Maria; Haribhakti, Aditi; Patel, Purvi; Cani, Eris; Choi, Seohyun (Claudia); Jagpal, Sugeet; Varughese, Tilly; et al.
Abstract : IMPORTANCE: COVID-19 can cause serious illness requiring multimodal treatment and is associated with secondary infections. Studies have suggested an increased risk of fungal infections, including candidemia following severe COVID-19 though understanding of risk factors and clinical outcomes remains unclear. OBJECTIVES: To describe clinical characteristics, outcomes and risk factors of candidemia among patients hospitalized with severe COVID-19. DESIGN, SETTING, AND PARTICIPANTS: A multicenter, case-control study of patients with severe COVID-19 was conducted to evaluate risk factors and clinical outcomes in patients who developed candidemia between August 2020 and August 2021. MAIN OUTCOMES AND MEASURES: Chart review evaluating institutional and patient demographics, clinical and mycological characteristics, concomitant interventions (antibiotics, immunosuppressive agents, parenteral nutrition, degree of oxygen support, mechanical ventilation, surgery), treatment regimens, and outcomes (length of stay and discharge disposition) RESULTS: A total of 275 patients were enrolled in the study, including 91 patients with severe COVID-19 and subsequent candidemia and 184 with severe COVID-19 without candidemia. Most patients received antibiotics prior to candidemia episode (93%), while approximately one-quarter of patients received biologic for COVID-19. In-hospital mortality was significantly higher in the cases compared with the controls (68% vs 40%; p < 0.01). Candida albicans was the most common (53%), followed by C. glabrata (19%). Use of central lines, biologic, and paralytics were independent risk factors for candidemia. CONCLUSIONS AND RELEVANCE: Candidemia following COVID-19 infection is a concern that requires clinical consideration and patient monitoring. Risk factors for the development of candidemia in the setting of COVID-19 infection are largely consistent with traditional risk factors for candidemia in hospitalized patients.